Targeting NF-κB signaling cascades of glioblastoma by a natural benzophenone, garcinol, via in vitro and molecular docking approaches - Rizvi, Syed Mohd Danish; Almazni, Ibrahim A.; Moawadh, Mamdoh S.; Alharbi, Zeyad M.; Helmi, Nawal; Alqahtani, Leena S.; Hussain, Talib; Alafnan, Ahmed; Moin, Afrasim; Elkhalifa, AbdElmoneim O.; Awadelkareem, Amir Mahgoub; Khalid, Mohammad; et al. (Frontiers in Chemistry, 2024)
Activation of Nuclear Factor kappa-B (NF-κB) is a frequent phenomenon in cancers, which results in the hyper expression of NF-κB target genes, and leads to malignant transformation, metastatic dissemination, abnormal cellular proliferation or resistance to programmed cell death. Glioblastoma Multiforme (GBM) is regarded as the most aggressive form of brain tumor delineated by high cellular heterogeneity, and resistance towards conventional therapeutic regimens. In this study, our findings throw light on the anti-cancer potential of Garcinol, a naturally derived benzophenone, was assessed against GBM. During the analysis, we observed a noteworthy reduction in the viability of rat glioblastoma C6 cells at a concentration of 30µM of the extract (p<0.001). Exposure to the garcinol also induced nuclear fragmentation and condensation, as evidenced by DAPI-stained photomicrographs of C6 cells. The dissipation of mitochondrial membrane potential in a dose-dependent fashion was linked to the activation of caspases. Furthermore, it was observed that garcinol mediated the inhibition of NF-κB (p<0.001), and decreased the expression of also modulated the expression of NF-κB associated genes for genes associated with cell survival (Bcl-XL, Bcl-2 and survivin) and proliferation (cyclinD1). Moreover, garcinol showed interaction with NF-κB through some important amino acid residues such as Pro 275 , Trp 258 , Glu 225 , and Gly 259 during molecular docking analysis.Comparative analysis with positive control (temozolomide) was also performed. Summarily, the garcinol induced apoptotic cell death via inhibiting NF-κB activity in C6 cells, thus implicating it as a plausible therapeutic agent for GBM.